Missed nursing care measured by MISSCARE Survey - the first pilot study in the Czech Republic and Slovakia - Renáta Zeleníková; Elena Gurková; Darja Jarošová (University of Ostrava, 2019)
Aim: The aims of the pilot study were a) to compare the amount, type, and reasons for missed nursing care in the Czech Republic and Slovakia; and b) to investigate the psychometric properties of the Slovak and Czech versions of the MISSCARE Survey. Design: Cross-sectional study. Methods: For measurement of missed nursing care The Missed Nursing Care (MISSCARE) Survey was used. The sample consisted of 226 hospital nurses in the Czech Republic and Slovakia. Results: The internal consistency of Part A measured by Cronbach alpha was 0.939 for the Czech version and 0.945 for the Slovak version of the MISSCARE Survey. The average score for missed nursing care was 1.64 ± 0.51 for the Czech Republic, and 1.99 ± 0.83 for Slovakia. Shortfalls in labor resources were cited as the chief reason for missed nursing care in the countries surveyed. Conclusion: Psychometric testing showed that the Czech and Slovak versions of the MISSCARE Survey are reliable and valid tools, and can be used for measuring missed nursing care.